Lymnaea columella: two new Brazilian localities in the states of Amazonas and Bahia - W. Lobato Paraense (Memorias do Instituto Oswaldo Cruz, 1986)
The occurrence of Lymnaea columella is recorded in Tefé, Amazonas state, where it was found together with Drepanotrema anatinum, Physa marmorata and pomacea sp. L. columella was also collected in Salvador, Bahia state, at the dique do Tororó, an urban lake formely mentioned (as "lac Baril") by Moricand (1853) as a breeding-place of Biomphalaria glabrata, Drepanotrema cimex, D. depressissimum, Pomacea lineata, P. decussata and Ancylus moricandi. The four first-mentioned species, as well as physa cubensis and Hemisinus brasiliensis, were also collected now. This is the first record of a lymnaeid in the Northeastern region of Brazil. É registrada a ocorrência de Lymnaea columella em Tefé, Estado do Amazonas, onde foi encontrada juntamente com Physa marmorata e Pomacea sp. L. columella foi também coletada em Salvador, Estado da Bahia, no Dique do Tororó, lago urbano antes mencionado por Moricand (1853) como criadouro de Biomphalaria glabrata, Drepanotrema cimex, D. depressissimum, Pomacea lineata, P. decussata e Ancylus moricandi. As quatro primeiras espécies mencionadas, assim como Physa cubensis e Hemisinus brasiliensis, também foram agora coletadas. Este é o primeiro registro de um limneídeo na região Nordeste do Brasil